Model of gravitational effects in Saturn’s rings - Manchenko, L. D. (Одеські астрономічні публікації, 2019)
In this work, we consider one possi- ble gravitational interaction in a system consisting of Saturn, its satellites and rings. The structure of rings can be changed because of such interactions leading to some sculpting of rings. In consequence of not triv- ial gravitational effects, various perturbations are ob- served on the edges of rings. We use methods of ce- lestial mechanics to describe a system containing the planet, two satellites and the ring placed between them. In such a system, gravitational forces lead to running waves that deform the ring. These effects are peculiar to Saturn’s F ring. The description of these perturba- tions needs more difficult physical model. In particu- lar, to find the change in the ring’s edge it’s necessary to go to the non-inertial reference frame. To describe some effects we expect to employ methods of nonlinear physics to build the model.